2023
DOI: 10.1227/neu.0000000000002672
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Prehospital Management of Traumatic Brain Injury 3rd Edition: Executive Summary

Gregory W. J. Hawryluk,
Al Lulla,
Randy Bell
et al.

Abstract: Prehospital care markedly influences outcome from traumatic brain injury, yet it remains highly variable. The Brain Trauma Foundation's guidelines informing prehospital care, first published in 2002, have sought to identify and disseminate best practices. Many of its recommendations relate to the management of airway, breathing and circulation, and infrastructure for this care. Compliance with the second edition of these guidelines has been associated with significantly improved survival. A working group devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Since then, research focused on the prehospital setting and yielded some different conclusions: two large convincing RCTs indicated that TXA administration in pre-hospital does not help 6-month neurologic function recovery among severe TBI patients or even increased the mortality of severe TBI patients [7,8]. Thus, the newest prehospital TBI management guideline reminds readers of the judicious use of TXA [9]. Further studies on TXA administration are guaranteed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, research focused on the prehospital setting and yielded some different conclusions: two large convincing RCTs indicated that TXA administration in pre-hospital does not help 6-month neurologic function recovery among severe TBI patients or even increased the mortality of severe TBI patients [7,8]. Thus, the newest prehospital TBI management guideline reminds readers of the judicious use of TXA [9]. Further studies on TXA administration are guaranteed.…”
Section: Introductionmentioning
confidence: 99%
“…As intracranial hemorrhage (ICH) is a common but complicated commodity for severe TBI, to prevent increased intracranial pressure (ICP) leading to brain herniation, guidelines, and studies suggest both TXA using and the timely, fast, and large dose of dehydration agent administration for active TBI-related ICH during prehospital-transferring [9,10,11]. However, as the dehydration and the anti-brinolytic are…”
Section: Introductionmentioning
confidence: 99%